Relationship between pulmonary hypertension, peripheral vascular calcification, and major cardiovascular events in dialysis patients - Sun Chul Kim; Hyo Jung Chang; Myung-Gyu Kim; Sang-Kyung Jo; Won-Yong Cho; Hyoung-Kyu Kim (The Korean Society of Nephrology, 2015)
Background: Pulmonary hypertension (PHT) is a recently recognized complication of chronic kidney disease. In this study, we investigated the association between PHT, peripheral vascular calcifications (VCs), and major cardiovascular events. Methods: In this retrospective study, we included 172 end-stage renal disease (ESRD) patients undergoing dialysis [hemodialysis (HD)=84, peritoneal dialysis=88]. PHT was defined as an estimated pulmonary artery systolic pressure>37 mmHg using echocardiography. The Simple Vascular Calcification Score (SVCS) was measured using plain radiographic films of the hands and pelvis. Results: The prevalence of PHT was significantly higher in HD patients (51.2% vs. 22.7%). Dialysis patients with PHT had a significantly higher prevalence of severe VCs (SVCS≥3). In multivariate analysis, the presence of severe VCs [odds ratio (OR), 2.68], mitral valve disease (OR, 7.79), HD (OR, 3.35), and larger left atrial diameter (OR, 11.39) were independent risk factors for PHT. In addition to the presence of anemia, severe VCs, or older age, the presence of PHT was an independent predictor of major cardiovascular events in ESRD patients. Conclusion: The prevalence of PHT was higher in HD patients and was associated with higher rates of major cardiovascular events. Severe VCs are thought to be an independent risk factor for predicting PHT in ESRD patients. Therefore, in dialysis patients with PHT, careful attention should be paid to the presence of VCs and the occurrence of major cardiovascular events.